2016
DOI: 10.1103/physrevb.93.195301
|View full text |Cite
|
Sign up to set email alerts
|

Spin transport inn-type single-layer transition-metal dichalcogenides

Abstract: Valley asymmetry of the electron spectrum in transition metal dichalcogenides (TMDs) originates from the spin-orbit coupling. Presence of spin-orbit fields of opposite signs for electrons in K and K valleys in combination with possibility of intervalley scattering result in a nontrivial spin dynamics. This dynamics is reflected in the dependence of nonlocal resistance on external magnetic field (the Hanle curve). We calculate theoretically the Hanle shape in TMDs. It appears that, unlike conventional materials… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…As a result of averaging out of ±B SO the − mode has a long lifetime, ∼ Ω form of S x (t) in the domain Γ > 1 is still the sum of the products of oscillating and exponentially decaying functions, as we have demonstrated in Ref. [42]. This allows to calculate the Hanle curve explicitly for finite separation, d, between the contacts.…”
Section: B the Case Of Fast Intervalley Scatteringmentioning
confidence: 91%
See 4 more Smart Citations
“…As a result of averaging out of ±B SO the − mode has a long lifetime, ∼ Ω form of S x (t) in the domain Γ > 1 is still the sum of the products of oscillating and exponentially decaying functions, as we have demonstrated in Ref. [42]. This allows to calculate the Hanle curve explicitly for finite separation, d, between the contacts.…”
Section: B the Case Of Fast Intervalley Scatteringmentioning
confidence: 91%
“…In our earlier paper Ref. [42] we have demonstrated that the analytical solution of the system depends on the dimensionless ratio…”
Section: Theorymentioning
confidence: 99%
See 3 more Smart Citations